Comunidades essenciais, legiões demoníacas: multidão, literatura e riqueza comum - Alemar Silva Araújo Rena (2015)
The objective of this thesis is to reflect on the multitude from an ontological, political and aesthetic point of view, with reference to the different outlooks literature and other multitudinous linguistic practices can offer. At stake is a critique of some trends in modern thought or politics that frequently devised the multitude - legion of desiring bodies and singularities - as impotent mass or essential communities and thus suspended the production of the commonwealth. Antagonizing these trends, the determination that moves us is how to conceive, in the realm of language production, immaterial economy or biopolitics, the possibilities of an open and constituent communality that does not precede itself, but revolves around a non-essential, non-teleological, collaborative and multitudinous assemblage (agencement) that produces the common as it produces itself. We defend that, if the multitude has been seen as demonic throughout modernity, it is not because it is an affront to the ideal of real democracy or the production of the commonwealth, but precisely on the contrary, because it often turns this ideal into a tangible, immanent and 'monstrous' alternative to the transcendence of law and capital. Drawing on an expressly cartographic methodology, we intend to bring to surface not only some aporias that haunted the mind and the imagination in view of the political emergence of the modern crowds, but also concepts and claims that today become central to thinking critically the production of language in a way that exceeds notions that face a profound crisis of meaning - progress, civilization, peoples, identity, class, cultural industry, copyright, canon, etc.